Board Performance of Fisheries Graduates: Logistic Regression Analysis for Curriculum Enhancement - Nora M Matusalem; Marcial M Bandoy; Chester Alexis C Buama; Karen A Manaig; Alberto D Yazon (Research Synergy Foundation, 2024)
This study investigates the factors affecting the board performance of Bachelor of Science in Fisheries (BSFi) graduates in the fisheries technologists licensure exams in a specific region of the Philippines. The impetus for this research arose from observed variations in exam performance among graduates, prompting an examination of educational and institutional influences on success. The study used a purposive sampling technique to gather data from 138 respondents across State Universities and Colleges (SUCs) who took their first licensure exam from October 2018 to October 2023. A validated online survey questionnaire assessed academic performance, teaching methods, curriculum, faculty qualifications, library resources, laboratory facilities, and student characteristics. Logistic regression analysis was employed to analyze the relationship between these independent variables and licensure exam performance. The findings of this study are of profound importance, as they reveal strong correlations between faculty qualifications and exam outcomes, emphasizing the need for continuous professional development. Moreover, the study identifies improved laboratory facilities and a robust curriculum as critical factors contributing to student success. These insights have the potential to significantly impact stakeholders, informing them about essential areas for intervention and improvement. Ultimately, they aim to elevate the educational experience and licensure performance of BSFi graduates, thus supporting their professional trajectories in the fisheries sector.